Emotional regulation and the occurrence and course of hypertension - Piotrowska-Półrolnik, Małgorzata Agnieszka; Krejtz, Izabela; Holas, Paweł (Journal of Education, Health and Sport, 2017)
This article aims to draw attention to the role of psychological factors in morbidity, progression, as well as in the treatment of hypertension. Psychological factors, especially how a person regulates negative emotions, can contribute to the increased risk of cardiovascular disease or exacerbation of these diseases. Over the past several decades, many data have been collected showing the relationship of psycho-emotional factors to the development and development of somatic diseases, including hypertension. More and more research shows that emotional regulation is associated with the occurrence and severity of hypertension. The consequence of this knowledge is the search for psychosocial interventions that could lead to a reduction in blood pressure in hypertensive people. Among them, preliminary research deals with such interventions as meditation training including transcendental meditation, slow breath training, and Mindfulness-Based Stress Reduction (MBSR) training. In these training sessions hope is also given in cases where it is difficult to normalize the pressure values with only normotensive drugs.